A Novel Technique to Isolate and Detect Jamming Attack in MANET - Kaur, Harkiranpreet; Kaur, Rasneet (International Journal of Computer Sciences and Engineering, 2025)
MANET is infrastructure less, decentralized multi hope network where the nodes are randomly to move in any direction, there each node works as a router and host to send packet to each other, there is no any requirement of fixed infrastructure. There are many security threats in MANET. Various types of attacks can be easily triggered in the network. So MANET has a security issue. In this paper we have discussed about Jamming attack in AODV protocol. Due to this attack network performances degrade. Therefore a novel technique has been proposed to detect and isolate jamming attack in the network using monitoring nodes.